Mass vegetative propagation of rare and endangered tree species of Indonesia by shoot cuttings by KOFFCO method and effect of container type on nursery storage of rooted cuttings - HENTI HENDALASTUTI RACHMAT; ATOK SUBIAKTO; ARIDA SUSILOWATI (Society for Indonesian Biodiversity, 2018)
Rachmat HH, Subiakto A, Susilowati A. 2018. Mass vegetative propagation of rare and endangered tree species of Indonesia by shoot cuttings by KOFFCO method and effect of container type on nursery storage of rooted cuttings. Biodiversitas 19: 2353-2358. The Forestry Research and Development Agency (FORDA) and The Advance Research of Komatsu Ltd have developed a mass propagation technique using shoot cuttings, namely KOFFCO system (Komatsu-FORDA Fog Cooling System). KOFFCO system controls environmental factors (temperature, humidity, and light intensity) to produce high percentage of rooted cuttings. The seed production of dipterocarp species is unreliable and unpredictable. Thus, vegetative propagation is an alternative means for producing planting materials of dipterocarp species. An attempt was made to produce rooted cuttings of rare and endangered dipterocarp and non-dipterocarp species of the Indonesian native trees, for further use in both reforestation and plantation programs. In fact, this study attempts to answer two specific research questions: (i) What is the potential of KOFFCO system as a vegetative mass propagation technique for Indonesian dipterocarps and non-dipterocarps? (ii) What is the effect of container types on long-term post-nursery storage of dipterocarp planting stock? To answer the first question stated above, vegetative propagation through shoot cuttings of 24 species belonging to 7 genera of dipterocarps and 13 species belonging to 12 genera of non-dipterocarps was attempted (>30.000 cuttings, in total), using KOFFCO system. The results showed that KOFFCO is an efficient innovative technology for the successful mass propagation from cuttings. 100% root formation obtained for Nauclea orientalis, Anotephalus macrophyllus and Ficus sp. To find the answer for the second question, storage experiments and growth observations of the planting stock of selected dipterocarp species was performed, using three different types of containers. Rooted cuttings of six species of dipterocarps with same germination date were tested in each type of the container. The result showed that medium sized square and medium sized round containers produced an average height increment of 19.92 cm and 21.58 cm, respectively, in a year, while small sized square containers produced only 13.94 cm height increment. Both square and round shaped containers are appropriate for short term storage of planting stock, while small containers are more appropriate for storing planting stocks or seedlings for a longer period.